The effect of some office papers quality characteristics on offset printing process - SÖNMEZ, SİNAN (My University, 2022)
This study was aimed to examine the effects of basic properties, fiber morphological properties, strength properties, wettability and optical properties on offset printing of office papers. Widely used office papers with different brands were obtained from Istanbul-Turkey. Technical characteristics of papers; basic properties, strength properties including tensile, burst, tear, and Z direction tensile strength and optical properties such as gloss, whiteness, opacity, and wettability tests were determined according to TAPPI and ISO standards. The results obtained by the tests are as follows; i) there is a great difference in water resistance between the top and the lowest values (207 %), ii) there is little difference between the highest and the lowest brightness value (3.8 %), other papers values have close to each other, iii) in the printing process there is a little difference between the highest, and the lowest gloss values (36.7 %), although the others are close iv) the highest and lowest values in CIE C* showed that it ranged from the narrowest color gamut to the widest color gamut. By applying the widely used offset printing process to commercially produced office papers, the quality levels were evaluated to raise awareness of consumers and sellers.
Keywords: Mühendislik ve Teknoloji; Engineering and Technology; MALZEME BİLİMİ, KAĞIT & AHŞAP; Malzeme Bilimi; Mühendislik, Bilişim ve Teknoloji (ENG); MATERIALS SCIENCE, PAPER & WOOD; MATERIALS SCIENCE; Engineering, Computing & Technology (ENG); General Materials Science; Physical Sciences; office papers; offset printing; optical properties; strength properties; wettability; STARCH; PENETRATION; SUBSTRATE; STRENGTH